Post-Traumatic Stress Disorder and associated factors among adolescents after 2015 Nepal Earthquake - Mishra, Durga; Giri, Deena; Marahatta, Sujan Babu (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: On April 25, 2015 at 11:56 local time, a great earthquake of massive magnitude-7.8 trembler was experienced in Nepal. Along with the physical and economical loss, such disasters can have devastating consequences in adolescent’s mental health. The purpose of this study is to determine the prevalence of Post-Traumatic Stress Disorder and associated factors among adolescents after 2015 Nepal Earthquake. Methods: A total of 140 adolescents from grade 8, 9 and 10 of two higher secondary schools were recruited in this study. Post-Traumatic Stress Disorder CheckList-5 (PCL-5) of DSM-V criteria was used for the diagnosis of Post-Traumatic Stress Disorder. Chi-square test was used to assess the association. Results: Among 140 adolescents, the age range was 12 to 19 years with a mean age of 14.8 (SD=1.1) where 27.1% of the participants had Post-Traumatic Stress Disorder. A statistically significant association was found between Post-Traumatic Stress Disorder and grade (χ² = 9.324, p<0.01), earthquake exposure (χ² =32.251, p<0.001) and death of someone close in earthquake (χ² = 9.535, p<0.01). Majority of the respondents reported symptoms of avoiding memories, thoughts, or feelings related to the stressful experience (58.57%). Conclusions: This study hopes to assist the therapist, psychiatrists and planners in the design and implementation of effective and appropriate intervention programs that can help reduce the impact of Post-Traumatic Stress Disorder on adolescents, aid in psychological reconstruction and decrease the long term negative mental health consequences of such disasters especially for those who are at lower grade, were exposed to earthquake and lost their close people in the earthquake. Journal of Manmohan Memorial Institute of Health Sciences Vol. 3, No. 1, 2017, page: 45-55